Freeports como importante ferramenta econômica: análise de perspectiva para implantação em território brasileiro - Bandeira, Luana da Costa (2022)
The existing Freeports in the world, especially in Europe, have played an important role for the global economy, in view of the commercial circulation. Tax benefits, ease of transactions, data and even property protection, and the difficulty for inspection intervention are some of the main factors that attract most consumers to Freeports. Those interested in using the services offered by Freeports are owners of great fortunes (HNW People), of valuable goods that find in these warehouses the necessary security to keep their rare objects indefinitely and with tax exemptions that earn them a lot of money. In this way, the present work aims to analyze the international customs legislation and Comparative Law regarding the activities carried out within the luxury warehouses, highlighting the economic influence, especially for the art market, in addition to examining the possibility of installation in Brazilian lands. , considering both current regulations and local demand. The research used the methodological mechanism of the bibliographic review of specialized literature, exploring the risks arising from characteristics such as confidentiality and data protection, which favor illegalities such as tax evasion, money laundering, forgery of works of art., financing of terrorism, among others, as well as observing, on the other hand, the growing data of international trade, influenced by the activity of the warehouses. In this way, based on norms such as the Customs Regulation (Decree nº 6.759/2009), the General Agreement on Tariffs and Trade (Gatt-1994), the Revised Kyoto Convention, Resolutions of the European Parliament and the United States Senate, it is an analysis of crime prevention policies, especially money laundering, which also has a history with the art market. On the other hand, technological development is observed as a way of inserting effective supervision by government authorities into the modus operandi of activities carried out within the Freeports. The cases revealed by investigative operations such as the Panama Papers, Paradise Papers, Pandora Papers, among others, as well as the Geneva, Singapore and Luxembourg Freeports, are analyzed as a way of identifying regulatory parameters and technical methods of combating organized crime through the use of these luxury warehouses. In the meantime, it is intended to bring feasible solutions to develop the discussion in order to face the persistent advances of criminality and try to preserve the cultural history of the nations, as well as to develop the debate regarding the expansion of Freeports, as an important economic tool, to other countries, including Brazil.